Functional analysis of A 5' untranslated variant in rhodopsin : implications for the retinitis pigmentosa phenotype - Akinyi, Maureen Veronica (Division of Human Genetics, 2014)
Retinitis Pigmentosa (RP) is a group of heterogeneous retinal degenerative diseases that predominantly affect rod photoreceptor cells. Symptoms include night blindness and gradual peripheral vision loss, which progresses to a complete loss of vision. Clinical, phenotypic and genetic heterogeneity are frequently observed in RP. Mutations in Rhodopsin (RHO) have been identified as a major cause of RP. A sequence variant identified in the 5' untranslated region of RHO, g.269A>G, also known as c.-26A>G, was proposed to increase the risk of developing RP. In this study, the functional effect of this variant, individually and in cis with known pathogenic variants, was investigated using mammalian cell lines in order to determine whether the variant is a modifier of disease phenotype.